2012
DOI: 10.4314/agrosh.v11i1.10
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic Responses of Cowpea (<i>Vigna unguiculata</i>) Inoculated with Cucumber Mosaic Virus to Soil Amendment with Neem Leaf Powder

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…These setbacks have made the quest for alternative approaches to the pest control including plant products, very expedient (Lale, 2002). Currently, global research efforts now support the development of plant products with proven crop protection potentials (Aliyu et al, 2011). Rahman and Talukder (2006) reported that grains mixed with leaf, seed powder, or plant extracts reduced oviposition, inhibited damage and suppressed adult emergence of C. maculatus.…”
Section: Introductionmentioning
confidence: 99%
“…These setbacks have made the quest for alternative approaches to the pest control including plant products, very expedient (Lale, 2002). Currently, global research efforts now support the development of plant products with proven crop protection potentials (Aliyu et al, 2011). Rahman and Talukder (2006) reported that grains mixed with leaf, seed powder, or plant extracts reduced oviposition, inhibited damage and suppressed adult emergence of C. maculatus.…”
Section: Introductionmentioning
confidence: 99%
“…Five micro litre of β-mercapto-ethanol was added to the extract just before use (Adamu et al, 2015). The topmost leaves of 10-day-old Ife Brown seedlings were dusted with carborundum powder (Aliyu et al, 2011) (600-mesh), a piece of cotton wool was dipped in the BlCMV extract and the inoculum was gently rubbed on the upper leaf surface. Distilled water was then sprinkled on the inoculated leaves.…”
Section: Source Of Inoculum Maintenance and Inoculationmentioning
confidence: 99%
“…Nearly 75 to 80 % of world's groundnut is grown by resource poor smallholder farmers in developing countries who routinely obtain yields of 500 -800 kg ha -1 as opposed to the potential yields of >2.5 t ha -1 (Idem and Showemimo, 2005). Low yields are mainly due to numerous diseases caused by fungi, viruses, bacteria and nematodes (Arogundade et al, 2010;Aliyu et al, 2011;Osei et al, 2013). Diseases in groundnut caused by Blackeye cowpea mosaic virus (BICMV), Cucumber mosaic virus (CMV), Groundnut bud necrosis virus (GBNV), Groundnut rosette virus (GRV), Indian peanut clump virus (IPCV), Peanut clump virus (PCV), Peanut mottle virus (PeMoV), Peanut stripe virus (PStV), Tobacco streak virus (TSV) and Tomato spotted wilt virus (TSWV) are the most economically important and are responsible for serious yield losses globally or regionally (Taiwo, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Cowpea is an essential legume in Nigeria (Abayomi and Adeyini, 2005). The current world research efforts now supports the development of plant products with proven crop protection potentials compared to the use of chemicals which may be toxic to both the plants and environment (Aliyu et al, 2011). Bacteria play the central role in hydrocarbon degradation.…”
Section: Introductionmentioning
confidence: 99%